Naming of Children and Meaning of Names among the Akan of Ghana: Defining Identities? - Arko-Achemfuor, Akwasi (Southern African Journal for Folklore Studies, 2018)
This article examines the naming of children among the Akan, which as a form of identity, appears very complex to many across the world. The Akan are mostly located along the coastal and central regions of Ghana and the Ivory Coast, with some others in the diaspora who also claim ancestry. People who trace their roots and ancestry to the Akan continue to name children according to Akan traditions. The naming of children is of great importance in all Akan societies, as it is believed that the name given to a child can affect his behaviour and destiny. Besides, the family name that is given to the child the day the child is born is very significant as it actually becomes the first name of the person. The qualitative method of enquiry was used to gather data from respondents by means of interviews and observations on the significance and processes of naming children from four Akan communities in the Brong Ahafo and Ashanti Regions of Ghana. The findings shed light on the processes, significance, and meaning of a number of Akan names that are given to people in general, and children in particular.